Glasbeni video kot marketinško orodje glasbene industrije - Gutman, Maja (Monitor ISH, 2008)
While post-modern theories fail to explain the connection between the music video and the music industry, their findings may serve as a basis for reconsidering and redefining the place of the video in marketing and in everyday life. With the support of empirical data, we seek to show that the constant change in music video production has changed not merely the concept but even the medium of the music industry. Therefore we provide a brief historical survey stretching from the first music video to todayćs Internet video stars, including the local presence of MTV (MTV Adria) and its current position among the young and on the market.
Keywords: marketing; mass media; množični mediji; video; glasba; music; glasbena industrija; MTV; postmodernizem; potrošnja; blagovne znamke; MTV Adria